Association of Noise Annoyance with Measured Renal Hemodynamic Changes - Dennis Kannenkeril; Susanne Jung; Christian Ott; Kristina Striepe; Julie Kolwelter; Roland E. Schmieder; Agnes Bosch (Karger Publishers, 2021)
Background: Chronic mental stress is recognized as a modifiable risk factor for cardiovascular disease. The aim of this study was to demonstrate that noise annoyance-induced stress is associated with changes in renal hemodynamics. Methods: Renal hemodynamic parameters were measured using steady-state input clearance with infusion of para-aminohippuric acid and inulin in individuals with normal, high normal, and elevated blood pressure. All individuals ranked subjective annoyance due to noise in everyday life on a 7-grade Likert scale. The median of all rankings was used as a cutoff point to divide the group into noise-annoyed and non-noise-annoyed individuals. Different renal hemodynamic parameters were calculated based on the Gomez equation. Results: Noise-annoyed individuals (n = 58) showed lower renal plasma flow (599 ± 106 vs. 663 ± 124 mL/min, p = 0.009), lower renal blood flow (1,068 ± 203 vs. 1,172 ± 225 mL/min, p = 0.047), higher filtration fraction (22.7 ± 3.3 vs. 21.3 ± 3.0, p = 0.012), higher renal vascular resistance (88.9 ± 25.6 vs. 75.8 ± 22.9 mm Hg/[mL/min], p = 0.002), and higher resistance of afferent arteriole (2,439.5 ± 1,253.4 vs. 1,849.9 ± 1,242.0 dyn s−1 cm−5, p = 0.001) compared to non-noise-annoyed individuals (n = 55). There was no difference in measured glomerular filtration rate (133 ± 11.8 vs. 138 ± 15 mL/min, p = 0.181), resistance of efferent arteriole (2,419.4 ± 472.2 vs. 2,245.8 ± 370.3 dyn s−1 cm−5, p = 0.060), and intraglomerular pressure (64.0 ± 3.1 vs. 64.6 ± 3.5 mm Hg, p = 0.298) between the groups. After adjusting for age, renal plasma flow, renal blood flow, and renal vascular resistance remained significantly different between the groups, with a trend in increased afferent arteriolar resistance and filtration fraction. Conclusion: In this study, noise annoyance was associated with reduced renal perfusion attributed to increased renal vascular resistance predominantly at the afferent site. Long-term consequences of this renal hemodynamic pattern due to noise annoyance need to be investigated.